Ayah Asi di Media Online - Totok Wahyu Abadi (el Hakim Press, 2018)
The purpose of this study is to analyze and explain the Ayah ASI in online media twitter and explained Ayah ASI in social semiotic perspective. Qualitative research, describes the situation or discourse about exclusive breastfeeding by the Ayah ASI. The method used is the MAK Halliday's social semiotic analysis that includes the text, the context of the situation (field of discourse, tenor of discourse, mode of discourse) and registers. The results of this study show that Communities Ayah ASI in his twitter @ID_AyahASI build knowledge to fathers and Indonesian mothers who still adhered to the old paradigm about things related to breastfeeding mothers who proves a lack of understanding and support dad. The father and mother who still believe the myths that inhibit the release of breast milk, do not have an understanding of the function of the hormone oxytocin for stimulation and lactation very clearly proves that knowledge or understanding of a mother and her husband support the most important factor in the success of breastfeeding. Ayah ASI twitter account with a non-formal language as well as a brief change views of mothers and fathers about the importance of breastfeeding to infants.